Study the polymorphism in UCSNP43, 44 to exon 3 of Calpain-10 gene of Polycystic Ovary Syndrome women in Thi Qar Province - E. Mahmood, Alia; Abdul Kareem Jabbar , Enas; G. Magtooph, Majida; Hashim, Mohammed (University of Thi-Qar Journal of Science, 2019)
The correlation between polycystic ovary syndrome (PCOS) and type-2 diabetes mellitus (T2DM) was reported regarding T2DM genes, which contribute in the pathogenesis of PCOS. The current study was aimed to investigate the association of CAPN-10 gene UCSNP-43, UCSNP-44 polymorphism with PCOS.Thirty women with PCOS and 20 healthy, which are matched in their age, were selected to test the anthropometric and biochemical profile of our samples. Nucleic acid of samples was extracted and genotype analysis was done. The results of patients-hormonal analysis were indicated that the level of follicle stimulating hormone was low and the levels of other hormones were high in comparison to that of healthy women. Biomass (BMI) and lipid profiles of PCOS patients were higher than from these in healthy women. Haplotypes of sequenced samples were determined for each gene fragment. The same three haplotypes of SNPs-43 were identified in both PCOS and controls samples. On the other hand, high diversity of haplotypes was found from SNPs-44. The meta-analysis with fixed and random effects odds ratio (ORs) on the basis of haplotypes frequencies were presented.